2013
DOI: 10.3174/ajnr.a3605
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic MR Imaging Patterns of Cerebral Fat Embolism: A Systematic Review with Illustrative Cases

Abstract: SUMMARY: Different MR imaging patterns of cerebral fat embolism have been reported in the literature without a systematic review. Our goal was to describe the patterns, explore the relationship between disease course and the imaging patterns, and discuss the underlying mechanism. We reveal 5 distinctive MR imaging patterns: 1) scattered embolic ischemia occurring dominantly at the acute stage; 2) confluent symmetric cytotoxic edema located at the cerebral white matter, which mainly occurs at the subacute stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
78
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 24 publications
1
78
0
Order By: Relevance
“…The white matter lesions occur mainly due to venous sludging and oedema. (1) There is usually a time lag between the pulmonary and CNS symptoms whose time duration depends on the filter effect (time taken for the passage of emboli from the pulmonary to the systemic circulation). The onset of neurological symptoms is therefore faster and much worse in patients with right-to-left shunts, such as in cases of patent foramen ovale.…”
Section: Discussionmentioning
confidence: 99%
“…The white matter lesions occur mainly due to venous sludging and oedema. (1) There is usually a time lag between the pulmonary and CNS symptoms whose time duration depends on the filter effect (time taken for the passage of emboli from the pulmonary to the systemic circulation). The onset of neurological symptoms is therefore faster and much worse in patients with right-to-left shunts, such as in cases of patent foramen ovale.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of numerous hypointensities predominantly in the white matter on susceptibilityweighted or gradient echo (GRE) sequences is considered to be pathognomic for microhemorrhages, and can also be seen in 60-88% of the acute to late stages of cerebral FES [5,[10][11][12]. These correlate with the petechial cerebral hemorrhages observed on autopsy [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, in retrospect, the "starfield" pattern seen on the MRI solidifies the diagnosis of FES, rather than a TMA. In cases of cerebral FES, a "starfield" pattern on diffusion-weighted MRI is seen, consisting of numerous punctuate foci in the white and grey matter, suggesting the presence of acute microinfarcts caused by the emboli [4][5][6][7]. Given the "starfield" pattern with microhemorrhages seen on our patient's MRI, and a cardiac emboli source ruled out by echocardiogram, it is likely that his neurologic abnormalities were due to cerebral FES rather than due to cerebral vaso-occlusion from a TMA.…”
mentioning
confidence: 99%
“…The classical starfield appearance on diffusion-weighted MRI imaging represents cytotoxic edema due to fat emboli. A recent systemic review revealed that scattered cytotoxic edema is the most common image finding of acute CFES, present in 84.6 % patients [6].…”
Section: Discussionmentioning
confidence: 99%